Hybridisation of two ductile materials – Steel fibre and self-reinforced polypropylene composites. (September 2017) - Swolfs, Y.; De Cuyper, P.; Callens, M.G.; Verpoest, I.; Gorbatikh, L.
Abstract: Hybridisation of self-reinforced polypropylene (SRPP) with ductile steel fibres is proposed as a way to create composites with a high stiffness, failure strain and toughness. The stiffness and yield stress of SRPP were significantly increased without sacrifice of toughness, even after normalisation to the composite density. The measurements revealed a higher stress level and slope after yielding than the predictions by the linear rule-of-mixtures. This effect was attributed to differences in the Poisson contraction of the two constituents and was supported by modelling predictions. The absolute penetration impact resistance of SRPP was increased, whereas the specific impact resistance remained the same, despite the high density of steel fibres. Placing steel fibre layers on the outside of the laminate maximised the penetration impact resistance, as it allowed the steel fibres to exploit their full plastic potential. These results can guide the optimisation of other hybrid composites with two ductile fibres.